2021
DOI: 10.1101/2021.01.10.21249151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robotic RNA extraction for SARS-CoV-2 surveillance using saliva samples

Abstract: Saliva is an attractive specimen type for asymptomatic surveillance of COVID-19 in large populations due to its ease of collection and its demonstrated utility for detecting RNA from SARS-CoV-2. Multiple saliva-based viral detection protocols use a direct-to-RT-qPCR approach that eliminates nucleic acid extraction but can reduce viral RNA detection sensitivity. To improve test sensitivity while maintaining speed, we developed a robotic nucleic acid extraction method for detecting SARS-CoV-2 RNA in saliva sampl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…This agent has been widely used for sample collection and transport of various infectious agents [21][22][23]. Indeed, the group of Hamilton et al 2021 [24] reported this reagent improves the detection of SARS-CoV-2 RNA in saliva samples, by detecting the Spike protein at low Cq cycles compared to samples preserved without DNA/RNA Shield™ . Similarly, the group of Coryell et al 2021 [25] reported that DNA/RNA Shield™ gave the best results in terms of viral detection.…”
Section: Discussionmentioning
confidence: 99%
“…This agent has been widely used for sample collection and transport of various infectious agents [21][22][23]. Indeed, the group of Hamilton et al 2021 [24] reported this reagent improves the detection of SARS-CoV-2 RNA in saliva samples, by detecting the Spike protein at low Cq cycles compared to samples preserved without DNA/RNA Shield™ . Similarly, the group of Coryell et al 2021 [25] reported that DNA/RNA Shield™ gave the best results in terms of viral detection.…”
Section: Discussionmentioning
confidence: 99%
“…We designed and implemented a saliva specimen collection pipeline that minimized exposure risk and maximized ease of use for participants. In parallel, we developed a high-throughput automated qPCR-based laboratory procedure for testing saliva for the presence of SARS-CoV-2 genetic material [2].…”
Section: Saliva Sample Choice and Study Designmentioning
confidence: 99%
“…tube with the station worker. From here, the samples were brought back to the IGI Diagnostics Lab, where they underwent the procedures outlined in [2].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations